Effective office ergonomic intervention: a study of work related musculo-skeletal disorders among the office workers of Katsina State Local Governments of Nigeria - Wee, Seow Ta; Mohamed, Sulzakimin; Gambo, Abdu (American Scientific Publishers, 2018)
Work place safety and health are issues of both global and local concern as work-related musculo-skeletal disorders account for over 40% of safety hazards which develop as a result of repetitive work place activities. Reports have shown that cases of work related musculo-skeletal disorders are very common among the office workers in the Nigerian civil Service (Public Sector) with negative consequences on the workers’ output and the economy in general. Due to the neglect and underfunding of Local Government offices in Nigeria, the offices are equipped with poor work facilities which continue to expose the workers to higher risk of work related musculoskeletal discomfort. Therefore, the main objective of this research is to determine the extent of work related to musculo-skeletal disorders among the Local Government employees of Katsina State in relation to the nature of their work place facilities. The methodology of the study is questionnaire adapted and modified from Cornell Musculo-skeletal Discomfort Questionnaire (CMDQ) and the Observational Checklist developed from previous studies of work place ergonomic. The result of the research shows that workers associated with computer and typing jobs in Katsina Local Government offices in Nigeria are exposed to work place ergonomic risk due to poor office facilities. Moreover, work related musculo-skeletal disorders such as back pains, neck disorder, shoulder pains, pains in the wrist and substantial cases of eye syndrome which are classified as part of musculoskeletal disorder are the risks that the workers encountered. Therefore, it is concluded that the poor nature and designs of work facilities in Katsina Local Government offices has forced workers to assume awkward work postures which is a good predictor for the prevalence of work related musculo-skeletal disorders. Hence, a great need for effective intervention so as to reduce the prevalence of work related musculo-skeletal disorders among the workers for a productive and sustainable office work environment.